탄소가치를 고려한 산림관리 최적화 방안 - 이상민 (한국농촌경제연구원, 2011)
This study is designed to find an optimized forest management scheme in preparation for inclusion of the value of carbon abatement in existing forest stands. Schemes to mitigate climate change by protecting forests include reforestation, afforestation and efficient forest management to maximize carbon absorption. The rotation period is extended if the value of carbon absorption as well as the timber values are considered for the stands of pine trees and Korean pine trees. The current management scheme is also analyzed and compared with optimal solutions. The result shows that in the case of pine trees the rotation period is optimal with the current method. But the rotation period decreases and the function value (objective value) increases if the optimal scheme is applied. The reason is that late execution of second thinning brings about slow progress of volume increment and extends the rotation period. If the rotation period is extended the present value from stands is discounted more seriously. To enhance the value of stands, the current rotation should be shortened, and the thinning should be executed at a time. In the case of Korean pine trees, the current rotation period is too short, and it is not optimal even under the current management method. Under the optimal management scheme, however, the rotation period becomes shorter than the current method. This happens because the current method includes four times of silvicultural treatments, and they last until 35 years after plantation. The cost of the treatments could not be recovered until after 100 years of plantation. Hence it is necessary to reduce the frequency of cutting and the age of final cutting. The simulation results show that the rotation period becomes shorter if the discount rate increases, and it becomes longer if the price of carbon dioxide increases. It is well known that the rotation period increases if the public values are added to the stands. However, it is also possible to find an optimal management scheme by adjusting the frequency and time of silvicultural treatments. Consequently, it could not be an optimal method of forest management to apply long and flat rotation periods even if some public values are added, but it is necessary to adjust and apply various rotation periods according to treatment numbers and cutting ages of different species.
Keywords: 기후변화; 산림관리체계; 탄소; 최적산림관리체계; climate change; forest management scheme; carbon; optimal forest management scheme